Laboratory Methods of Determination of Pore Structure Parameters: Formation Factor and Tortuosity of Permeable Media by Electric Methods - Łukowski, J.; Kaczmarek, M. (Engineering Transactions, 2002)
paper presents the methods of determination of structural parameters of porous materials: formation factor and tortuosity, based on conductometric techniques. The basic experimental procedures are reviewed and factors, which influence the relative conductivity of electrolyte saturated samples such as type of experimental technique, electrolyte and electrodes, length of sample, are presented. The role of surface conductance, polarization effects and frequency are analyzed.